A comparative analysis of Amsterdam and Singapore´s smart living and smart people strategies - Coppard, Dylan William (2023)
This paper explores Singapore's renowned Smart City model and its potential applicability to a European city. Through a comprehensive analysis of six dimensions, including interviews with industry experts, the study researches the key success factors driving Singapore's Smart City Model. Next, using a data-driven funnel process, Amsterdam was selected as the most suitable European city for comparison. The comparative analysis reveals distinct approaches to Smart City development and identifies mutual learning opportunities, specifically focusing on the dimensions of Smart People and Living.